The Influence Of Pricing Rate And Word Of Mouth (Wom) Mediated By Trust On Credit Car Purchasing Decisions - Soegeng Wahyoedi; Andry (International Journal of Science, Technology & Management, 2021)
Intense competition between finance companies makes each must apply the best strategy to become a winner. This study aims to analyze the direct effect of pricing rate and word of mouth (wom) on purchasing decisions and indirectly mediated by trust, as well as the direct influence of trust on purchasing decisions. The population of this study is consumers who have purchased a car on credit at Maybank Finance in the West Java area, which consists of 4 city branches, namely: Bandung, Bogor, Cirebon and Karawang, both those that have been paid off and those that are still running. Samples were taken as many as 100 respondents using non-probability sampling technique with quota sampling method. Data analysis using Partial Least Square (PLS) using SmartPLS software. The results show that all hypotheses are proven to have an influence on pricing rate, word of mouth (wom) and trust on purchasing decisions, and it is also proven that trust is able to mediate the relationship between these variables.